Dark Tourism as a Niche Form of Cultural Tourism - Beata REFORMAT (Communications of International Proceedings, 2025)
The aim of this article is to present dark tourism as an important, though often controversial, element of contemporary tourism, with particular emphasis on its educational and cultural potential in the context of niche forms of tourism. A methodology drawing on the methodological canon of management sciences was used, enabling conceptual and theoretical research opportunities. This was the basis for a critical analysis of foreign and Polish literature on the subject, including specialist journals and current reports on the phenomenon under study. Descriptive methods, case studies, and observation were used to interpret and analyze the collected material. The article demonstrates that dark tourism, despite its controversial nature, constitutes an important niche form of cultural tourism, which is gaining increasing importance in tourism practice and research. The conclusions from the analyses suggest the need for further research on the ethical dimensions and impact of dark tourism on tourists' historical awareness.
Keywords: dark tourism; cultural tourism; niche form of tourism